Antioxidant Activities and Profile of Amino Acid of Yoghurt from Beef Milk Fermentation with Dadih Starter - Sri Yadial Chalid; Pratiwi Nur Kinasih; Fitriah Hatiningsih; Tarso Rudiana (Syarif Hidayatullah State Islamic University, 2021)
Dadih is naturally fermented buffalo milk in bamboo tubes and known to have antioxidant, antibacterial, and antihypertensive activity. Lactic acid bacteria in dadih can use as a starter to produce yogurt. The study aimed to produce yogurt of cow's milk with dadih as a starter, to determine the antioxidant activity and amino acid composition. Dadih is added with concentration variation of 2.5; 5; 7.5 and 10% (v/v) and it fermented for 48 hours at room temperature. Lactic acid bacteria cell counts of dadih were calculated by the total plate count method. Yogurt was tested by organoleptics with 33 panelists and proximate analysis water, ash, fat and protein contens based on the Association of Official Analytical Chemist (AOAC) in 2005. Antioxidant activities of yogurt were tested by DPPH method (1,1-diphenyl-2-picrylhydrazyl). Amino acid composition of yogurt was analyzed using ultra performance liquid chromatography (UPLC). The research result of amount of LAB on dadih are 1.01 x 1011 CFU/mL, has fulfilled the requirements of SNI 2981: 2009. Yogurt produced with the addition of dadih by 10% (v/v) is most accepted by panelists. The highest antioxidant activity was obtained by yogurt with 2.5% addition of dadih with IC50 value of 78.28 ppm. Yogurt almost contain all essential and non-essensial amino acids including tyrosine and phenylalanine as the antioxidants. Measurement of water, ash, protein and fat content in the sample meets the requirements of SNI 2981: 2009.